Strategi Host Live Tiktok Dalam Membangun Keterhubungan Emosional Dengan Penonton - Eceh Trisna Ayuh; Lely Arrianie; Evi Hafizah; Marlinda Irwanti (STAI Bumi Silampari, 2026)
The live streaming phenomenon on TikTok has created a new form of interaction between content creators and viewers, requiring hosts to establish a strong emotional connection within a short timeframe. This issue is significant because emotional connection serves as a key factor in maintaining viewer engagement and loyalty in highly competitive digital environments. This study aims to analyze the strategies employed by TikTok live hosts to build emotional connections with their audiences and sustain active participation during live sessions. A descriptive qualitative research method was used, involving a literature review that analyzed various academic sources regarding digital communication and social media. Erving Goffman’s dramaturgical theory was applied to understand how hosts perform on the